MANAJEMEN PEMBELAJARAN BERDIFERENSIASI DALAM MENINGKATKAN HASIL BELAJAR IPAS DI SEKOLAH DASAR KABUPATEN CIANJUR: - Supyan Sauri; Gunawan, Nomi; Nurhayati; Mansyuriah, Siti Maryam; Susilawati; Yayi Solihah DM (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research analyzes the implementation of differentiated learning management to improve learning outcomes in Science, Social Studies, and Arts (IPAS) for fifth-grade elementary school students in Cianjur Regency. The background for this study is the importance of learning that accommodates the diverse characteristics of students, in line with the Merdeka Curriculum, which emphasizes a differentiated approach and holistically considers student wellbeing. Studies on differentiated learning management within the context of IPAS and its relationship to improving learning outcomes and student wellbeing in elementary schools are still limited. This research aims to uncover the role of structured and contextual differentiated learning management in improving IPAS learning outcomes, as well as its contribution to a learning environment that supports students' emotional and academic welfare. Using a qualitative method with a case study approach, data was collected through observation, in-depth interviews, and documentation. Data analysis was conducted in stages and interactively, including data reduction, data presentation, and conclusion drawing. The research findings indicate that effective differentiated learning management can enhance active participation, conceptual understanding, and academic achievement of students in IPAS. This approach also contributes positively to student wellbeing, as evidenced by an increase in self-confidence, independence, and learning satisfaction.